Diversity patterns and community characteristics of the fish assemblage of a West African lagoon - ASSOU, Délagnon; SEGNIAGBETO, Gabriel Hoinsoudé; Lederoun, Djiman; DENDI, Daniele; KETOH, Guillaume Koffivi K.; LALEYE, PHILIPPE A.; LUISELLI, Luca (My University, 2018)
Coastal lagoons are important habitats in West Africa, being also irreplaceable for many species of fish. The community structure and the diversity patterns of their fish assemblages have however been poorly studied so far. In order to evaluate the community structure and diversity metrics of fish assemblages of one of these lagoons (Lake Togo, Togo), we surveyed four stations that were different in terms of morphological and ecological characteristics, from July to September 2017. The fishing gears were recorded and catches of small-scale fisheries were analyzed. A total of 40 species in 37 genera, 24 families and 10 orders were recorded, with Cichlidae (six species), followed by Eleotridae (five species) and Gobiidae (three species) being the most diverse families. The most abundant species in the catches were: Sarotherodon melanotheron, Coptodon guineensis, Chrysischthys nigrodigitatus and Ethmalosa fimbriata. Strict estuarine species (Es) were the most represented forms in the catches. Calculated indices of diversity showed that Lake Togo has moderate diversity and a poor organization of individuals within species.
Keywords: fish fauna; community metrics; ecology; Lake Togo